Patient-centered care and the electronic health record: exploring functionality and gaps. Issue 3 (29th October 2020) - Butler, Jorie M; Gibson, Bryan; Lewis, Lacey; Reiber, Gayle; Kramer, Heidi; Rupper, Rand; Herout, Jennifer; Long, Brenna; Massaro, David; Nebeker, Jonathan
Abstract: Objective: Healthcare systems have adopted electronic health records (EHRs) to support clinical care. Providing patient-centered care (PCC) is a goal of many healthcare systems. In this study, we sought to explore how existing EHR systems support PCC; defined as understanding the patient as a whole person, building relational connections between the clinician and patient, and supporting patients in health self-management. Materials and Methods: We assessed availability of EHR functions consistent with providing PCC including patient goals and preferences, integrated care plans, and contextual and patient-generated data. We surveyed and then interviewed technical representatives and expert clinical users of 6 leading EHR systems. Questions focused on the availability of specific data and functions related to PCC (for technical representatives) and the clinical usefulness of PCC functions (for clinicians) in their EHR. Results: Technical representatives ( n  = 6) reported that patient communication preferences, personalized indications for medications, and end of life preferences were functions implemented across 6 systems. Clinician users ( n  = 10) reported moderate usefulness of PCC functions (medians of 2–4 on a 5-pointy -35t scale), suggesting the potential for improvement across systems. Interviews revealed that clinicians do not have a shared conception of PCC. In many cases, data needed to deliver PCC was available in the EHR only in unstructured form. Data systems and functionality to support PCC are under development in these EHRs. Discussion and Conclusion: There are current gaps in PCC functionality in EHRs and opportunities to support the practice of PCC through EHR redesign.